UNCITRAL MODEL LAW ON ELECTRONIC COMMERCE AND MODEL LAW ON ELECTRONIC SIGNATURES - Gunawan Widjaja; Kevin Neil McVey; Jestin Justian; Theresia Vena (Cross-border, 2018)
Whereas in analyzing the Model Law on Electronic Commerce and Electronic signatures, the author can see that there is a suggestion that must be conveyed carefully. In this modern era, the Indonesian government needs to review the provisions of its electronic commerce. That although the Model Laws are not a role model for regulations that need to be obeyed absolutely, they are a reflection to fill the legal void or ambiguity in our national law (rechtsvacuum). It is better for the government to continue to fill the void by being given a role model first, which can be used as a spur in producing better e-commerce provision products in the future.